THE IMPACT OF MECHANISTIC STRUCTURE ON ORGANIZATIONAL COMMUNICATION SATISFACTION IN A HIGHWAY CONCESSIONAIRE COMPANY IN MALAYSIA: A Case Study of Grand Saga Sendirian Berhad - Md Nordin, Shahrina; mohammed, halib; Ghazali, Zulkipli (Intellectbase International Consortium, 2010)

(untitled)
There is an on-going debate on the kind of organizational structure that promotes open and healthy communication. Some argue that hierarchical structure complicates the communication flow but others argue that a clear hierarchy limits confusion by knowing who is in charge. This study examines the impact of a mechanistic organizational structure on the organizational communication satisfaction in a highway concessionaire company in Klang Valley, Malaysia. The mechanistic organizational structure which is highly bureaucratic in nature is illustrated by the degree of formalization in the organization as perceived by the employees. Organizational communication, a multidimensional construct, is examined through the employees’ perceptions of their degree of satisfaction in the communication climate, upward communication, downward communication, horizontal communication, organizational perspective and organizational integration. A set of questionnaire was administered to employees at all levels in the organization to collect the data. The study revealed that formalization does have a positive impact on organizational communication satisfaction in the organization.